Software modules for operational forecasts of effective dose of workers in the acute phase of NPP accident - Kryuk, Юлианна (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2014)
The need of the operational forecasting of effective doses to workers in order to improve emergency preparedness was considered. The mathematic models of effective exposure dose assessments of personnel in the emergency situations were given. The possibilities of the use case of the software by the user and its modular structure were defined, the implementation platform was chosen. The program module allows no special skills to perform predictive assessment of effective doses of the personnel in the acute phase of the accident was created.